Alpha Decay Half-Lives Calculation of Even-Even Nuclei in the62≤Z≤100Region using Woods-Saxon Potential - rizal kurniadi; Chumaira Ramadani (Indonesian Journal of Physics, 2022)
Alpha decay properties of even-even nuclei in the 62 ≤ Z ≤ 100 region are investigated within the Unified Fission Model based on a Modified Woods-Saxon potential. The computed alpha decay half-lives are compared to experimental data and are found to be in good agreement with it. The acquired pattern of the variation of alpha decay half-lives as a function of neutron number are explained by the nuclear shell effect. The experimental alpha decay energy Q is found to have an inverse relation with the alpha decay half-lives. This work has shown that the Unified Fission Model based on a Modified Woods-Saxon potential is sufficient to obtain the values of alpha decay half-lives.